2011
DOI: 10.1161/strokeaha.110.596163
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Baseline Blood Pressure Parameters (Including Mean Pressure, Pulse Pressure, and Variability) and Early Outcome After Stroke

Abstract: Background and Purpose-High blood pressure (BP) in acute stroke is associated independently with a poor outcome.Recent evidence suggests that other hemodynamic parameters may also be associated with outcomes following stroke. Methods-The relationship between baseline BP, heart rate, and other hemodynamic parameters, and early outcomes were assessed using data from TAIST trial. Results-Death or neurological deterioration at day 10 was associated, both in unadjusted and adjusted analyses, with systolic BP (adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 7 publications
2
69
1
Order By: Relevance
“…Many researchers have published data for the possible fluctuation of BP in patients with stroke, and various studies have shown that the increase of BP values after stroke is transient (1) and associated with a poor outcome (11,12,13,14). Elevated BP usually decreases spontaneously in the next few days after the stroke onset, without the application of antihypertensive therapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have published data for the possible fluctuation of BP in patients with stroke, and various studies have shown that the increase of BP values after stroke is transient (1) and associated with a poor outcome (11,12,13,14). Elevated BP usually decreases spontaneously in the next few days after the stroke onset, without the application of antihypertensive therapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing blood pressure through angiotensin was also demonstrated to increase the mean arterial pressure by 40-60% and reduce infarct volume after transient MCAo in rats (Chileuitt et al, 1996). While mild induced hypertension may be neuroprotective, it is important to note that chronic hypertension worsens stroke outcome (Aslanyan et al, 2003;Geeganage et al, 2011;Toyoda et al, 2009), possibly due to inhibition of collateral blood flow. In spontaneously hypertensive rats, compensatory growth of leptomeningeal collaterals in response to chronic cerebral hypoperfusion is impaired relative to normotensive rats, though this compensatory growth is restored by anti-hypertensive therapies (Omura-Matsuoka et al, 2011).…”
Section: Augmenting Cerebral Blood Flow By Inducing Mild Hypertensionmentioning
confidence: 97%
“…The natural history is for BP to decline spontaneously over the subsequent several days. Elevated BP is associated with poor outcome, whether defined as recurrent stroke, early death, or death and disability several months after stroke onset [3][4][5]. There is however, limited and conflicting evidence regarding the benefits of BP lowering treatment in acute stroke, with some large studies reporting near positive effects on functional outcome [6], but others reporting neutral [7,8,9], or near negative results [10].…”
Section: Introductionmentioning
confidence: 99%